Pengembangan Aplikasi Layanan Cyber Counseling Terintegrasi Website Berbasis Android - Baharudin Yusup Budiman; Agus Wibowo; Hadi Pranoto (Counseling Milenial (CM), 2025)
Cyber counselling is a kind of professional counselling in which the client and counsellor are physically separated but yet able to connect with one another via the use of the internet and other technological means. The study's goal is to determine whether clients may benefit from the information services offered by an Android app that is linked to the Cyber Counselling website. Quantitative and qualitative methods are used by researchers while gathering data. Teachers and students who work in the field of guiding and counselling provided the data for this study. Ten pupils were utilised as part of the study's sample. Interviews, observations, and written records are all valid methods of data collecting. Using data analysis methods, we can evaluate the scalability and viability of our application products. Data analysis performed by subject matter experts revealed an 80% compliance with the "feasible" criterion. Experts in the media evaluated the validation findings and determined that all of them met the "very feasible" standards. Eighty percent of the criteria for "feasible" were met in the assessment of validation findings by language specialists. Expert practitioners obtained a 92% feasibility rating for the validation findings, while students' feedback on the cyber counselling app was rated as "very feasible" by 90.18 percentage points. This study concludes that Guidance and Counselling teachers can use the Cyber Counselling Application to support the implementation of counselling services in schools, allowing students to receive virtual assistance with their problems without having to physically visit the guidance and counselling room.